Pendampingan Belajar Matematika Bagi Anak-Anak Di Panti Asuhan Medan Indonesia - Dedi Holden Simbolon; Eka Kartika Silalahi; Joen Parningotan Purba; Theresia Perbina; Mery Kristiani Rajagukguk (CV. Multi Kreasi Media, 2023)
The aim of this activity is to foster participants' interest and attraction in learning Mathematics by using interactive media properly and correctly. Assistance is carried out by a service team consisting of 3 lecturers and 2 PGSD Study Program students. Children who are provided with assistance include kindergarten, elementary, middle school children. This PKM activity was carried out at the Sinar Abadi, Karya Ramlan, dan Cinta Kasih Nurani Orphanage, Medan City, North Sumatra. Data collection used in this activity is: (1) performance test questions to measure mastery of mathematics. Participants take tests individually and are given at the end of the learning material. and (2) field notes, carried out by documenting the learning process and photos of activities during the teaching and learning process both before and during the action. The output targets to be achieved from this activity are increasing the knowledge of partners/heads of orphanages in educating children in orphanages and publication of scientific articles in community service journals